SURGICAL MANAGEMENT OF DEPIGMENTATION IN HYPERPIGMENTATION WITH SCRAPPING METHOD USING SURGICAL SCALPEL : Penatalaksanaan Bedah Depigmentasi pada Hiperpigmentasi dengan Metode Scrapping Menggunakan Scalpel Bedah - Ida Bagus Nyoman Dhedy Widyabawa; Agus Gede Sutamaya (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2021)
Introduction: The color of healthy gingiva is often influenced by melanin pigmentation as an abnormal deposition of melanocytes located in basal and suprabasal cells. Gingival hyperpigmentation that exceeds normal causes a variety of physiological and pathological conditions. Gingival depigmentation is a periodontal surgical procedure to remove or reduce gingival hyperpigmentation by various techniques to improve aesthetics. The procedures include the use of chemicals such as 90% phenol, diamond drill abrasion, gingivectomy, soft tissue autograft, partial thickness flap, cryosurgery and laser. Case: A 19-year-old male patient came to periodontist office, after an examination he had Smoker's melanosis hyperpigmentation in the upper anterior region. Case Management: The patient was given depigmentation surgery using the scrapping method using a scalpel No. 15c. Discussion: Surgical management of gingival depigmentation with scrapping provides good esthetic results. Conclusion: It is necessary to take a proper history and adequate examination and be wise in determining the various surgical methods of depigmentation.